Impact of centralization of prostate cancer services on the choice of radical treatment. (8th July 2022) - Aggarwal, Ajay; Han, Lu; Tree, Alison; Lewis, Daniel; Roques, Tom; Sangar, Vijay; van der Meulen, Jan
Abstract : Objective: To assess the impact of centralization of prostate cancer surgery and radiotherapy services on the choice of prostate cancer treatment. Patients and Methods: This national population‐based study used linked cancer registry data and administrative hospital‐level data for all 16 621 patients who were diagnosed between 1 January 2017 and 31 December 2018 with intermediate‐risk prostate cancer and who underwent radical prostatectomy (RP) or radical radiation therapy (RT) in the English National Health Service (NHS). Travel times by car to treating centres were estimated using a geographic information system. We used logistic regression to assess the impact of the relative proximity of alternative treatment options on the type of treatment received, with adjustment for patient characteristics. Results: Of the 78 NHS hospitals that provide RT or RP for prostate cancer, 41% provide both, 36% provide RT and 23% provide RP. Compared to patients who had both treatment options available at their nearest centre where overall 57% of patients received RT and 43% RP, patients were less likely to receive RT if their nearest centre offered RP only and the extra travel time to a hospital providing RT was >15 min (52% of patients received RT and 48% RP%, odds ratio [OR] 0.70 (0.58–0.85); P < 0.001). Conversely, patients were more likely to receive RT if their nearest centre offered RT and the extra travel time to a hospital providing RP was >15 min (63% of patients received RT and 37% RP, OR 1.23 (1.08–1.40); P < 0.001). There was a negligible impact on the type of treatment received if centres providing alternative treatment options were ≤15‐min travel time from each other. Conclusion: The relative proximity of prostate cancer treatment options to a patient's residence is an independent predictor for the type of radical treatment received. Centralization policies for prostate cancer should not focus on one treatment modality but should consider all treatments to avoid a negative impact on treatment choice.